Respuesta :
nice, already in vertex form
y=a(x-h)^2+k
(h,k) is vertex
therfor since (-3,6) is vertex
we are looking for something like
y=a(x-(-3))^2+6 simplified to
y=a(x+3)^2+6
A is ansre
y=a(x-h)^2+k
(h,k) is vertex
therfor since (-3,6) is vertex
we are looking for something like
y=a(x-(-3))^2+6 simplified to
y=a(x+3)^2+6
A is ansre
So,
The vertex form of a parabola is:
[tex]y=a(x-h)^2+k[/tex]
and the vertex is at (h,k).
Thus, the equation will have to look something like this:
[tex]y=a(x+3)^2+6[/tex]
Only option A matches these criteria, so is must be the correct option.
The vertex form of a parabola is:
[tex]y=a(x-h)^2+k[/tex]
and the vertex is at (h,k).
Thus, the equation will have to look something like this:
[tex]y=a(x+3)^2+6[/tex]
Only option A matches these criteria, so is must be the correct option.